PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR - Elvina Elvina (STKIP ROKANIA, 2016)
The study is in the form of classroom action research (PTK). Broadly speaking, the implementation of the PTK is done in four stages: planning, implementation, observation and reflection. This research was conducted in the second semester, the subject of this study is elementary school students Va classes totaling 27 students. The instrument used for data collection in this study is the observation sheet activities of teachers and students during the learning process and learning outcomes in the form of test replicates the end of each cycle is given in the form of an objective. The results showed that the application of PBI learning model can improve student learning outcomes IPA, the average value of 79.44 students in the first cycle and the second cycle increased to 90.48. This means that the application of the model PBI can improve student learning outcomes IPA